Towards in-service training needs of secondary school agriculture teachers in a paradigm shift to outcome-based education in Uganda. Issue 5 (20th October 2017) - Okiror, John James; Hayward, Geoff; Winterbottom, Mark
ABSTRACT: Purpose: This paper examines the in-service teacher training needs of secondary school agriculture teachers in Uganda as the country moves towards an 'outcome-based' education by removal of subjects and instead, uses learning areas, presenting a need for new pedagogical skills among teachers. Design/methodology/approach: A cross-sectional survey was conducted in Uganda between June and September 2016 to assess the teaching methods and teacher training needs for secondary school agriculture curriculum. Data were collected from 80 agriculture teachers and 57 administrators from 60 secondary schools, randomly drawn from 25 districts in Uganda. The data were analysed with descriptive statistics. Findings: The findings show that there about 10 key competences required by the teachers to thrive in their profession. These range from traditional classroom teaching to community outreach and linkages with agribusinesses which is in tandem with outcome-based education beyond the classroom walls. Respondents highlight lack of practical agriculture skills and exposure to the modern farming practices. Theoretical implications: This paper examines role of formal in-service teacher training based on theory of change and proposes using professional learning communities for school-level improvements. Practical implication: The results were not significant enough to warrant strong recommendations. However, they suffice to highlight a growing need for in-service teacher support mechanism for a dynamic subject like agriculture using communities of practice at school and district levels. Originality/value: In the current context of growing concern for unemployment in Africa, secondary schools will require competent teachers to engage students into transferable learning, given that it is the terminal level of education for majority.